2009
DOI: 10.1038/jid.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Mediates Sphingosylphosphorylcholine-Induced Itch-Associated Responses in Mouse Skin

Abstract: In atopic dermatitis, the concentration in the skin of sphingosylphosphorylcholine (SPC), which is produced from sphingomyelin by sphingomyelin deacylase, is increased. In the present study, we investigated the itch-eliciting activity of SPC and related substances and the mechanisms of SPC action in mice. An intradermal injection of SPC, but not sphingomyelin and sphingosine, induced scratching, an itch-associated response, which was not suppressed by a deficiency in mast cells or the H(1) histamine receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…However, the role of leukotrienes or prostaglandins in chronic dermatitis induced by repeated application of oxazolone is unclear so far. It has been reported that the 5-lipoxygenase inhibitor zileuton and the 5-lipoxygenase activating protein inhibitor MK-866 suppress itchassociated behavior induced by several pruritogens in mice (15,35,36). Furthermore, the oxazolone-induced severe scratching behavior was completely suppressed by pretreatment with zileuton, but not the cyclooxygenase inhibitor indomethacin or the platelet-activating factor-receptor antagonist YM264.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of leukotrienes or prostaglandins in chronic dermatitis induced by repeated application of oxazolone is unclear so far. It has been reported that the 5-lipoxygenase inhibitor zileuton and the 5-lipoxygenase activating protein inhibitor MK-866 suppress itchassociated behavior induced by several pruritogens in mice (15,35,36). Furthermore, the oxazolone-induced severe scratching behavior was completely suppressed by pretreatment with zileuton, but not the cyclooxygenase inhibitor indomethacin or the platelet-activating factor-receptor antagonist YM264.…”
Section: Discussionmentioning
confidence: 98%
“…32) Intradermal injection of SPc, but not of sphingomyelin and sphingosine, elicits scratching in mice. [32][33][34] SPc may act on the epidermal keratinocytes, dendritic cells, primary sensory neurons, and mast cells in the skin. [34][35][36] Naturally occurring d-erythro SPc, but not l-threo SPc, induces scratching after intradermal injection, raising the possibility that SPC acts on a specific receptor to induce itching.…”
Section: Lipid Mediatorsmentioning
confidence: 99%
“…[32][33][34] SPc may act on the epidermal keratinocytes, dendritic cells, primary sensory neurons, and mast cells in the skin. [34][35][36] Naturally occurring d-erythro SPc, but not l-threo SPc, induces scratching after intradermal injection, raising the possibility that SPC acts on a specific receptor to induce itching. 33) However, SPc receptors remain unclear, although some candidates were reported.…”
Section: Lipid Mediatorsmentioning
confidence: 99%
“…17,23,27) In healthy humans, naloxone increases itch thresholds to histamine. 18) In contrast, µ-opioid receptor agonists elicit facial scratching following intracisternal injection and body scratch- ; the failure of histamine to elicit scratching in mice (1974) 8) ; scratching induced by intracerebroventricular and intrathecal injections of bombesin in rats (1983); responses of primary afferents to cowhage stimulation in cats (1987) 10,11) ; scratching induced by injections of opioids into the medullary dorsal horn in monkeys (1992,1993); and scratching induced by injection of morphine into the medullary dorsal horn in rats (1995).…”
Section: Scratching Behaviors and Opioid Receptorsmentioning
confidence: 99%
“…Leukotriene B 4 is involved in the scratchinducing actions of other keratinocyte-producing substances such as sphingosylphosphorylcholine and nociceptin 27,114) (Fig. 4).…”
Section: )mentioning
confidence: 99%